The Impact of Immune Cells on the Skeletal Muscle Microenvironment During Cancer Cachexia - VanderVeen, Brandon N.; Murphy, E. Angela; Carson, James A. (Frontiers in Physiology, 2020)
Progressive weight loss combined with skeletal muscle atrophy is a common comorbidity associated with cancer that results in adverse consequences for the patient related to decreased chemotherapy responsiveness and increased mortality. Cachexia’s complexity has provided a barrier for developing successful therapies to prevent or treat the condition, since a large number of systemic disruptions that can regulate muscle mass are often present. Furthermore, considerable effort has focused on investigating how tumor derived factors and inflammatory mediators directly signal skeletal muscle to disrupt protein turnover regulation. Currently there is developing appreciation for understanding how cancer alters skeletal muscle’s complex microenvironment and the tightly regulated interactions between multiple cell types. Skeletal muscle microenvironment interactions have established functions in muscle response to regeneration from injury, growth, aging, overload-induced hypertrophy and exercise. This review explores the growing body of evidence for immune cell modulation of the skeletal muscle microenvironment during cancer-induced muscle wasting. Emphasis is placed on the regulatory network that integrates physiological responses between immune cells, with other muscle cell types including satellite cells, fibroblast cells, and endothelial cells to regulate myofiber size and plasticity. The overall goal of this review is to provide an understanding of how different cell types that constitute the muscle microenvironment and their signaling mediators contribute to cancer and chemotherapy-induced muscle wasting.